Determinant Factors of Depression in Patients with Coronary Heart Disease - Aan Nur'aeni; Ristina Mirwanti; Anastasia Anna; Ikeu Nurhidayah (Jurnal Keperawatan Padjadjaran, 2019)
Depression has been related to poor quality of life and recurrence in CHD patients. It is important to explore factors associated with the depression to prevent problems and to assist with appropriate intervention. Furthermore, the determinants of depression in CHD patients in Indonesia are still unknown. This study aimed to identify the determinants of depression in CHD patients in Indonesia. This study was a quantitative study with a cross-sectional approach. Samples were recruited from outpatient care in a referral hospital in Bandung using a consecutive sampling technique for a-2 month period (n=101). Data were collected using a questionnaire package consisting of a demographic questionnaire, Beck Depression Index [BDI] (II), Zung Self-rating Anxiety Scale, Seattle Angina Questionnaire, and Spirituality Index of Well-Being. Data were analyzed using mean, frequency distribution, chi-square and logistic regression analysis. In terms of its association with depression in CHD patients, low spiritual well-being had the highest odds ratio [OR] (OR = 9.3, 95% CI = 2.968 - 29.451, p <0.01); non-anxious state and medication history had low ORs (sequentially OR = 0.2, 95% CI = 0.067 - 0.644, p < 0.01; OR=0.2 95% CI = 0.062 - 0.772, p < 0.01);  PCI (percutaneous coronary intervention) with medication had the lowest OR value (OR = 0.02, 95% CI = 0.002 - 0.278, p <0.01). On the other hand,  unmarried status and male gender were identified as confounding variables. Low spiritual well-being was a major predictor of depression in CHD patients, whereas no anxiety, and history of medication, consist of CHD medication and reperfusion therapy contributed to a lower risk of depression. It is recommended to include strategies in improving spiritual well being and managing anxiety to reduce the risk of depression among CHD patients.